Trade union awareness and barriers among university support staff in Malaysia - Ismail, Fadillah; Wei, Chan Shiau; Xian, Lee Wei (Journal of Islamic, Social, Economics and Development, 2026)
Trade unions serve as an important mechanism for safeguarding employee welfare and strengthening collective voice at the workplace, including within higher education institutions. This paper focuses on trade union awareness and participation barriers among university support staff in Malaysia. It highlights how understanding of union roles, access to information, organizational communication climate, perceived union benefits, and management–employee relations influence willingness to join and engage in union activities. Key barriers include limited exposure to union functions and benefits, time and workload constraints, concerns about conflict or career implications, and perceptions that unions are not closely aligned with everyday work issues. Overall, the discussion underscores the need for more structured communication and education initiatives, alongside constructive union–management engagement, to enhance member participation, employee well-being, and stable industrial relations in universities.